LEVEL OF STUDENT LEARNING SATISFACTION WITH THE LEARNING EYES OF MEDIA PJOK IN PANDEMIC TIME COVID-19 - Andi Sultan Brilin S.E.Wahyudhi; Hofidz Parwansyah; Humaedi; Hendra Iskandar (Universitas Tadulako, 2021)
Based on the problems in this study, it focused on how the level of student learning satisfaction towards learning PJOK in MAN Toli-Toli during the Covid-19 pandemic. This study seeks to determine the level of satisfaction of each student with learning PJOK during the Covid-19 pandemic in MAN Toli-Toli. So that this research has the aim of knowing to what extent the level of student learning satisfaction through online media corner learning during the Covid-19 pandemic. This research is a survey research on students at MAN Toli-Toli. This type of research is descriptive qualitative. The instrument used in this study is in the form of a questionnaire containing statements to students, and students give a checklist (√). The frequency with the very satisfied category was 10 or 8%, the frequency with the satisfied category was 22 or 18%, while the highest value of the frequency with the less satisfied category was 83 or 69%, and the frequency with the very dissatisfied category was 5 or 4%, the level of student learning satisfaction through online media corner learning during the Covid 19 pandemic in Man Tolitoli based on the data table above as a whole in the less satisfied category. And it can be seen at the interval 72.46 to 100.48, so it can be concluded that the level of student learning satisfaction through online media corner learning during the Covid 19 pandemic in Man Tolitoli as a whole is less satisfied